English Vocabulary Enhancement Strategies for ESL Learners: A Study - Kottacheruvu, Nagendra (International Journal of Language and Literary Studies, 2023)
Students often spend hours studying through textbooks, practising grammatical exercises, and maybe even viewing the occasional streaming series in the target language in order to acquire proficiency in it. Many individuals, however, are unaware that working on vocabulary is just as crucial, if not more so, than working on grammar when it comes to learning a target language. However, those who do understand the need to learn vocabulary often come across numerous challenges in learning it. The main aim of this study was to investigate effective ways of learning and enhancing vocabulary through surveys and interviews with postgraduate students at Maulana Azad National Urdu University (MANUU).